Primary Salivary Human Stem/Progenitor Cells Undergo Microenvironment‐Driven Acinar‐Like Differentiation in Hyaluronate Hydrogel Culture. (18th August 2016) - Srinivasan, Padma Pradeepa; Patel, Vaishali N.; Liu, Shuang; Harrington, Daniel A.; Hoffman, Matthew P.; Jia, Xinqiao; Witt, Robert L.; Farach‐Carson, Mary C.; Pradhan‐Bhatt, Swati
Abstract: Radiotherapy for head and neck cancer often has undesirable effects on salivary glands that lead to xerostomia or severe dry mouth, which can increase oral infections. Our goal is to engineer functional, three‐dimensional (3D) salivary gland neotissue for autologous implantation to provide permanent relief. An immediate need exists to obtain autologous adult progenitor cells as the use of embryonic and induced pluripotent stem cells potentially pose serious risks such as teratogenicity and immunogenic rejection. Here, we report an expandable population of primary salivary human stem/progenitor cells (hS/PCs) that can be reproducibly and scalably isolated and propagated from tissue biopsies. These cells have increased expression of progenitor markers (K5, K14, MYC, ETV4, ETV5) compared with differentiation markers of the parotid gland (acinar: MIST1/BHLHA15 and AMY1A; ductal: K19 and TFCP2L1). Isolated hS/PCs grown in suspension formed primary and secondary spheres and could be maintained in long‐term 3D hydrogel culture. When grown in a customized 3D modular hyaluronate‐based hydrogel system modified with bioactive basement membrane‐derived peptides, levels of progenitor markers, indices of proliferation, and viability of hS/PCs were enhanced. When appropriate microenvironmental cues were provided in a controlled manner in 3D, such as stimulation with β‐adrenergic and cholinergic agonists, hS/PCs differentiated into an acinar‐like lineage, needed for saliva production. We conclude that the stem/progenitor potential of adult hS/PCs isolated without antigenic sorting or clonal expansion in suspension, combined with their ability to differentiate into specialized salivary cell lineages in a human‐compatible culture system, makes them ideal for use in 3D bioengineered salivary gland applications. Stem Cells Translational Medicine 2017;6:110–120